Predictors of entrepreneurial activity before and during the European economic crisis - Santos, Susana C. (2019)
The aim of this study is to analyze the role of individual characteristics and social norms as variables that explain early-stage entrepreneurial activity before and during the European crisis. We used the Global Entrepreneurship Monitor Adult Population Survey data from Southern European countries (Greece, Spain, Italy and Portugal) and Northern European countries (Sweden, Norway and Finland) in 2007, 2010, 2012 and 2013. We performed logistic regression analysis to identify the role of individual characteristics (self-efficacy, perceptions of opportunities, role model and risk perceptions) and social norms (desirable career choice, status and respect and public media) on the early-stage entrepreneurial activity (TEA). Results show that individual characteristics are the most important predictor of entrepreneurial activity, and this effect stays stable throughout the time of the crisis; and social norms have an absent or low effect on entrepreneurial activity, with slight fluctuations during the crisis. These results highlight the role of individual predictors on the entrepreneurial activity despite the macroeconomic environment, which empathizes the importance of education and training to promote the entrepreneurial mindset and attitude.